THE EDUCATIONAL VALUE OF WAYANG SANTRI KI HARYO ENTHUS SUSMONO IN THE PLAY "LUPIT KETEMU JODHO" - Agung Nugroho; Sri Prastiti Kusuma Anggraeni (Esteem Journal of English Education Study Programme, 2023)
The educational value of Ki Haryo Enthus Susmono's wayang santri in the play Lupit Ketemu Jodho needs to be known by the public. This study aims to determine the educational value of Ki Haryo Enthus Susmono's wayang santri in Lakon Lupit Ketemu Jodho. This research is a descriptive qualitative research. The data source of this research is the manuscript of the play Lupit Ketemu Jodho by Ki Haryo Enthus Susmono and the informant, Ki Haryo Enthus Susmono, who is the son of the late Ki Enthus Susmono. Data collection techniques used in this research are interviews and documentation. The data analysis technique used in this research is a qualitative analysis technique developed by Miles and Huberman which includes data reduction, data display, and conclusion drawing. The results showed that there are 6 educational values in Ki Haryo Enthus Susmono's wayang santri in Lakon Lupit Ketemu Jodho. These values are religious values (religious education), curiosity values (caring in society), tolerance values (in life understanding each other's friends), responsibility values (responsibility for their actions), friendly values (mutual friendship), and honest values (education in honesty).